Pogłoski w białostockim getcie. Przyczynek do historiografii Zagłady z perspektywy żydowskiej - Stoll, Kathrin (Zagłada Żydów. Studia i Materiały, 2012)
The article deals with rumors, which were circulated in the Białystok ghetto. It seems that a rumor is a form of collective interpretation of reality whose function is to structure equivocal situations by explaining events or predicting them. The mood and behavior of individuals and groups may be influenced by rumors, in particular if they find themselves – as the Jews in the ghettos – in an exceptional and lifethreatening situation characterized by insecurity, isolation and uncertainty. The article analyzes rumors relating to the deportations of Jews from the ghetto and German mass murder actions. It addresses the following questions: Which impact did the different rumors have? How did the Judenrat and the ghetto population react to them? The article demonstrates that Jews acted upon their apprehension or misapprehension of events and that their subjective evaluation of the German extermination policy influenced their behavior and decisions